Determinan job insecurity sumber daya manusia unit rekam medis di RSUD Masohi - Latumapina, Stella Florence Imanuela; Hosizah, Hosizah (Holistik Jurnal Kesehatan, 2025)
Background: Job Insecurity is a condition when employees feel threatened by their jobs and are powerless to do anything about the situation. Related to job insecurity, companies need to create a safe and comfortable work environment for their employees. Therefore, job insecurity must be immediately fixed by every company by reducing unsafe conditions. Purpose: To determine the determinants of job insecurity of human resources in the medical records unit. Method: Quantitative research with cross-sectional design. The population of the study was 29 employees of the medical record unit of Masohi Regional Hospital and data collection used multinomial logistic regression. Results: Most respondents experienced moderate job insecurity as much as 79.3%. The partial effect between age and job insecurity obtained a p value of 0.578, length of service with a p value of 0.333, education level with a p value of 0.010, and employment status with a p value of 0.00. Conclusion: The variables of education and employment status have a significant influence on job insecurity with a p value for the education variable of 0.010 and employment status of 0.007 (<0.05). Suggestion: Further research can consider additional variables such as working conditions, relationships between employees, and organizational culture in research on job insecurity.    Keywords: Job Insecurity; Human Resources; Medical Records Unit   Pendahuluan: Job Insecurity merupakan suatu keadaan ketika para karyawan merasa terancam oleh pekerjaannya dan tidak berdaya untuk melakukan apapun pada keadaan tersebut. Dalam hal job insecurity, perusahaan perlu untuk membuat sebuah lingkungan kerja yang aman dan nyaman bagi karyawannya. Oleh karena itu, job insecurity harus dapat ditingkatkan oleh setiap perusahaan dengan cara mengurangi kondisi yang tidak aman. Tujuan: Untuk mengetahui determinan job insecurity sumber daya manusia unit rekam medis. Metode: Penelitian kuantitatif dengan desain cross sectional. Populasi penelitian adalah 29 pegawai unit rekam medis di RSUD Masohi dan pengumpulan data menggunakan regresi logistik multinomial. Hasil: Sebagian besar responden mengalami job insecurity sedang sebanyak 79.3%. Pengaruh secara parsial antara usia terhadap job insecurity diperoleh p-value 0.578, masa kerja terhadap job insecurity p-value 0.333, pendidikan terhadap job insecurity p-value 0.010, dan status kepegawaian terhadap job insecurity p-value 0.00. Simpulan: Variabel pendidikan dan status kepegawaian memiliki pengaruh signifikan terhadap job insecurity dengan p-value pendidikan sebesar 0.010 dan status kepegawaian sebesar 0.007 (<0.05). Saran: Penelitian selanjutnya dapat mempertimbangkan variabel tambahan, seperti kondisi kerja, hubungan antar pegawai, dan budaya organisasi dalam studi job insecurity.   Kata Kunci: Job Insecurity; Sumber Daya Manusia; Unit Rekam Medis.